Effect of Stiffener Properties on Built-up CFS Column: Numerical Modelling using Finite Element Method - Anuar, Nazatul Izzati; Mohd Jaini, Zainorizuan (Recent Trends in Civil Engineering and Built Environment, 2022)
A cold-formed steel (CFS) column has become very common in low-rise building and portal steel frame system. However, built-up CFS column tendency to experiences buckling that directly affecting strength and displacement. Thus, the main objective of this study is to investigate the strength and displacement of built-up CFS column at different stiffener properties using finite element method (FEM) called WELSIM. The depth and thickness of stiffener was simulated to obtain various result. From the numerical modelling, it was observed that by increasing the stiffener properties, the ultimate strength will eventually increase. For failure mode, lobe buckling and flexural buckling occurs when the high force applied on the column. Therefore, the present of higher stiffener properties shows good result with the simulation result.